Effect of heat treatment to Clitoria Ternatea and Hibiscus Sabdariffa-based dye-sensitized solar cells characteristics - Nik Fatin Qistina, Amran; Wan Nur Ainna Amirah, Wan Zulkifli; Alyaa Afiqah, Fauzi; Siti Noor Hidayah, Mustapha; Ahmad Syahiman, Mohd Shah (IEEE, 2022)
In this paper, anthocyanin dyes produced from naturally occurring flowers of Clitoria ternatea and Hibiscus sabdariffa were used as sensitizers in dye-sensitized solar cells (DSSCs). The purpose of this study is to analyse the effect of pre-heat treatment towards the I-V performance of these two anthocyanins based-dye as natural dyes of Dye-Sensitized Solar Cell. The photovoltaic characteristics of Clitoria ternatea, Hibiscus sabdariffa and the combination of these flower-based dyes which supposedly produced a new purplish dye are investigated in this paper. The content of anthocyanin extracted from C. ternatea was evaluated using Ultraviolet-Visible Spectrophotometer (UV-VIS) to detect the light absorption behaviour. The performance of DSSCs was analysed with respect to the mix of anthocyanin-based extracts at varied pre-heated temperatures. Interestingly, the efficiency of C. ternatea-sensitized DSSC which the dye was pre-heated at 40 ° C increased significantly at almost 18 times higher than the C. ternatea’s sample with non-heated condition. In addition, a new mixture dye of H.sabdariffa and C. ternatea excelled good improved values of cell efficiency, short-circuit current density and fill factor with 0.0023%, 24.244 μA/cm2, and 37.17%, respectively, compared than that of other fabricated samples. This mixed extract exhibited the greatest sensitization in the cell, which was consistent with the extract's broadest spectrum